2022
DOI: 10.1021/jacs.2c04522
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-Up Approach to Understand Chirality Transfer across Scales in Cellulose Assemblies

Abstract: Cellulose is a polysaccharide that displays chirality across different scales, from the molecular to the supramolecular level. This feature has been exploited to generate chiral materials. To date, the mechanism of chirality transfer from the molecular level to higher-order assemblies has remained elusive, partially due to the heterogeneity of cellulose samples obtained via top-down approaches. Here, we present a bottom-up approach that uses well-defined cellulose oligomers as tools to understand the transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 54 publications
0
46
0
Order By: Relevance
“…cellulose 54,21 , chitin 54,21,47 , starch 45 , and glycogen 45 ) were prepared with full control over their length and sequence. Site specific modifications 21 were systematically introduced to establish structure-properties correlations and shine light on fundamental aspect of polysaccharide conformation and aggregation 108,109,110,111 . In this regard, the insertion of 13 C-or 19 Flabeled units permitted solution-phase NMR conformational studies, otherwise hampered by the severe chemical shift degeneracy of glycans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cellulose 54,21 , chitin 54,21,47 , starch 45 , and glycogen 45 ) were prepared with full control over their length and sequence. Site specific modifications 21 were systematically introduced to establish structure-properties correlations and shine light on fundamental aspect of polysaccharide conformation and aggregation 108,109,110,111 . In this regard, the insertion of 13 C-or 19 Flabeled units permitted solution-phase NMR conformational studies, otherwise hampered by the severe chemical shift degeneracy of glycans.…”
Section: Discussionmentioning
confidence: 99%
“…Site-specific modifications 21 were systematically introduced to establish structure-property correlations and to shine light on fundamental aspects of polysaccharide conformations and aggregation. [107][108][109][110] In this regard, the insertion of 13 C-or 19 F-labeled units permitted solution-phase NMR conformational studies, which are otherwise hampered by the severe chemical shift degeneracy of glycans. 52,53 Even so, many more glycosylation methodologies should be explored to expand the scope of glycan synthesis on solid-phase even further.…”
Section: Discussionmentioning
confidence: 99%
“…Due in part to the variability of the cellulose samples obtained via top-down methods, the process of chirality transfer from the molecular level to higher-order assemblies has remained mysterious to this point. To shed light on origin of chirality in CNCs, authors in ref 205 , suggested the use of well-defined cellulose oligomers as tools to explain how chirality is transferred from a single oligomer to supramolecular assemblies outside of a single cellulose crystal. This signifies that authors try to make CNC particles from their glucose precursors.…”
Section: Origin Of Chiralitymentioning
confidence: 99%
“…19,20 In contrast, bottom-up approaches guarantee precise saccharide sequences and patterns of modification, important determinants of the materials and biological properties. [21][22][23][24][25] Perturbing the primary sequence of an oligosaccharide with non-natural residues offers a strategy to systematically tune the macroscopic properties of a material. In addition, this approach provides indirect information on the role of the replaced unit (or functional group).…”
Section: Introductionmentioning
confidence: 99%
“…19,20 In contrast, bottom-up approaches guarantee precise saccharide sequences and patterns of modification, important determinants of the materials and biological properties. 21–25…”
Section: Introductionmentioning
confidence: 99%